Evolutionary processes and organizational adaptation : a Mendelian perspective on strategic management - Levinthal, Daniel A. (Oxford ; New York Oxford University Press, 2021)
This perspective also highlights the role of intentionality with respect to the selection and culling of strategic initiatives. The organization operates an (3z(Bartificial selection(3y (Benvironment, as firms receive profits and losses and, in turn, mediate how these environmental outcomes are projected onto underlying elements and actors within the organization. In this spirit, exploration can be considered not merely as the distance in the underlying behavior from current action, but also as changes in the dimensions of merit by which initiatives are judged. The Mendelian executive is a catalyst and cultivator of promising pathways to unknown futures.s
Keywords: Organizational change